State of the art multi-strategy improvement of Mg-based hydrides for hydrogen storage - Zhang, Jiguang; Zhu, Yunfeng; Yao, Linglong; Xu, Cheng; Liu, Yana; Li, Liquan (Journal of alloys and compounds, 2019)
As a representative light metal, magnesium is promising to be used as a hydrogen carrier owing to its high hydrogen capacity, low cost and natural abundance. The intrinsic drawbacks of MgH2 include the undesirable thermodynamic properties and sluggish sorption kinetics. In this paper, major progresses towards the practical use of magnesium as a hydrogen carrier are reviewed with a stress on the multi-strategy modifying techniques, including catalyzing, nanosizing, alloying, surface modification, amorphization and compositing. Current understanding of the fundamental principles governing the interaction of hydrogen with these light compounds is also summarized. Lights are shed on the coupling effect of the modifying methods through particular preparation methods. Integral performances of the modified MgH2 systems are compared from a strategical viewpoint. Experimental approaches, especially the pioneering techniques or methods, have been compared. Some difficulties of modifying Mg-based hydrides still remain, posing the following questions to us: how to prepare Mg-based intermetallic compounds with particle size below several nanometers? How to keep a well-established catalysis-enhancement mechanism or compositing synergistic effect through a more direct observation measurement? How to maintain chemical stability against environmental atmosphere? Future approaches about modifying MgH2 system, especially the enhancement of hydrogen storage performance, have been discussed. •Recent advances in Mg-based hydrogen storage materials have been reviewed.•Enhanced mechanisms of MgH2 were discussed, especially for the synergistic effect.•The coupling effect of different modifying strategies was highlighted.